DESIGN OF TILT TABLE FOR ABSOLUTE ACCELEROMETER CALIBRATION - Moh. Mambaul Ulum; Hapsoro Agung Nugroho; Marzuki Sinambela (Universitas Methodist Indonesia, 2023)
An accelerometer is used in applications that require measurements of absolute or relative acceleration. Tilt table (roll table) is a flat plane whose tilt can be changed. In BMKG (Climatology and Geophysics Meteorological Agency) there are two methods to calibrate accelerometer, namely calibration using relative sine waves and absolute calibration using the media acceleration due to gravity. The tilt table is used as an absolute accelerometer calibration aid. The tilt table uses a DC motor and gear ratio as the actuator to move so that the resolution of the angle changes on the axis of the tilt table will be smaller and smoother. The tilt table is able to assist the technician in calibrating the accelerometer with minimal angle movements so that the inclination settings at the time of calibration are more precise proved by the result of the comparison. The horizontal axis correction is 2,27o and the vertical is 2,31o.